Probiotics and yogurt modulate oxidative stress and fibrosis in livers of Schistosoma mansoni-infected mice - Manal F. El-Khadragy; Ebtesam M. Al-Olayan; Mohammed I. Y. Elmallah; Afra M. Alharbi; Hany M. Yehia; Ahmed E. Abdel Moneim (BMC Complementary and Alternative Medicine, 2019)
Abstract Background Considerable morbidity, mortality, and economic loss result from schistosomiasis infection. Deposition of Schistosoma eggs in the hepatic portal vein is considered as the main causative agent for the development of liver fibrosis and subsequent liver cirrhosis. Probiotics are exogenous and beneficial microorganisms to living hosts against the harmful effect of many parasites. Strong evidence suggests the importance of probiotics in the control strategy of helminth. The ultimate goal of this study is to evaluate the protective effect of probiotics and yogurt on Schistosoma mansoni-induced oxidative stress and hepatic fibrosis in mice. Methods Mice were infected by tail immersion of schistosomal cercariae followed by an oral treatment with either probiotics or yogurt for one week before infection and immediately post-infection. Mice were scarified on day 56 following infection with S. mansoni and liver sample were obtained. Results We showed that oral administration of probiotics or yogurt revealed a significant reduction in worm number, egg load, and granuloma size in liver tissue, which is mainly assigned to the decreased expression level of matrix metalloproteinases 9 (MMP-9) in liver tissue. A significant reduction in the oxidative stress markers-induced by S. mansoni infection including lipid peroxidation and nitrite/nitrate was also detected. The level of some antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase) and reduced glutathione was greatly enhanced. Furthermore, treatment with probiotics or yogurt inhibited apoptosis in hepatic tissue, which is mainly assigned to the decreased expression level of caspases-3 in liver tissue. Conclusion Our findings represent the promising anti-schistosomal activities of probiotics and yogurt.